Reg-2, A Downstream Signaling Protein in the Ciliary Neurotrophic Factor Survival Pathway, Alleviates Experimental Autoimmune Encephalomyelitis - Jiang, Hong; Tian, Ke-Wei; Zhang, Fan; Wang, Beibei; Han, Shu (Frontiers in Neuroanatomy, 2016)
Ciliary neurotrophic factor (CNTF), originally described as a neurocytokine that could support the survival of neurons, has been recently found to alleviate demyelination, prevent axon loss, and improve functional recovery in a rat model of acute experimental autoimmune encephalomyelitis (EAE). However, poor penetration into the brain parenchyma and unfavorable side effects limit the utility of CNTF. Here, we evaluated the therapeutic potential of a protein downstream of CNTF, regeneration gene protein 2 (Reg-2). Using multiple morphological, molecular biology, and electrophysiological methods to assess neuroinflammation, axonal loss, demyelination, and functional impairment, we observed that Reg-2 and CNTF exert similar effects in the acute phase of EAE. Both treatments attenuated axonal loss and demyelination, improved neuronal survival, and produced functional improvement. With a smaller molecular weight and improved penetration into the brain parenchyma, Reg-2 may be a useful substitute for CNTF therapy in EAE and multiple sclerosis (MS).